World Trade Organisation (WTO) and the Caribbean financial service sector. - BISSEMBER, Enid E. (1997)
Explores the impact of the liberalisation of trade in financial services on the financial services sector in the region. Advises that since such liberalisation is, or can be, affected by domestic variables as well as by global factors, policy makers should exercise caution when negotiating the trade in financial services agreement. Points out that the present situation in the WTO provides the Caribbean with an opening to assess carefully its financial services sector and develop its strategy for liberalization.